Influence of air-drying temperature on drying kinetics, colour, firmness and biochemical characteristics of Atlantic salmon (Salmo salar L.) fillets - Ortiz, Jaime; Lemus-Mondaca, Roberto; Vega-Gálvez, Antonio; Ah-Hen, Kong; Puente-Díaz, Luis; Zura-Bravo, Liliana; Aubourg, Santiago P. (Food Chemistry, 2013)
8 páginas, 2 tablas, 3 figuras In this work the drying kinetics of Atlantic salmon (Salmo salar L.) fillets and the influence of air drying temperature on colour, firmness and biochemical characteristics were studied. Experiments were conducted at 40, 50 and 60 °C. Effective moisture diffusivity increased with temperature from 1.08 × 10−10 to 1.90 × 10−10 m2 s−1. The colour difference, determined as ΔE values (from 9.3 to 19.3), as well as firmness (from 25 to 75 N mm−1) of dried samples increased with dehydration temperature. The lightness value L∗ and yellowness value b∗ indicated formation of browning products at higher drying temperatures, while redness value a∗ showed dependence on astaxanthin value. Compared with fresh fish samples, palmitic acid and tocopherol content decreased in a 20% and 40%, respectively, with temperature. While eicosapentaenoic acid (EPA) content remained unchanged and docosahexaenoic acid (DHA) content changed slightly. Anisidine and thiobarbituric acid values indicated the formation of secondary lipid oxidation products, which is more relevant for longer drying time than for higher drying temperatures. Peer reviewed